Large-Area and Ultrathin MEMS Mirror Using Silicon Micro Rim - Myeong-Su Ahn; Jaehun Jeon; Kyung-Won Jang; Ki-Hun Jeong (Micromachines, 2021)
A large-area and ultrathin MEMS (microelectromechanical system) mirror can provide efficient light-coupling, a large scanning area, and high energy efficiency for actuation. However, the ultrathin mirror is significantly vulnerable to diverse film deformation due to residual thin film stresses, so that high flatness of the mirror is hardly achieved. Here, we report a MEMS mirror of large-area and ultrathin membrane with high flatness by using the silicon rim microstructure (SRM). The ultrathin MEMS mirror with SRM (SRM-mirror) consists of aluminum (Al) deposited silicon nitride membrane, bimorph actuator, and the SRM. The SRM is simply fabricated underneath the silicon nitride membrane, and thus effectively inhibits the tensile stress relaxation of the membrane. As a result, the membrane has high flatness of 10.6 m−1 film curvature at minimum without any deformation. The electrothermal actuation of the SRM-mirror shows large tilting angles from 15° to −45° depending on the applied DC voltage of 0~4 VDC, preserving high flatness of the tilting membrane. This stable and statically actuated SRM-mirror spurs diverse micro-optic applications such as optical sensing, beam alignment, or optical switching.